Ring opening of 2-aza-3-borabicyclo[2.2.0]hex-5-ene, the Dewar form of 1,2-dihydro-1,2-azaborine: stepwise versus concerted mechanisms - Bettinger, Holger F.; Hauler, Otto (Beilstein Journal of Organic Chemistry, 2013)
The ring opening of the Dewar form of 1,2-dihydro-1,2-azaborine, 2-aza-3-borabicyclo[2.2.0]hex-5-ene (3) is investigated by theoretical methods by using multiconfiguration SCF (CASSCF) and coupled cluster theory [CCSD(T)] with basis sets up to polarised quadruple-zeta quality. The title compound was previously reported to form photochemically in cryogenic noble gas matrices from 1,2-dihydro-1,2-azaborine (4). Four reaction paths for the thermal ring opening of 3 to 4 could be identified. These are the conventional disrotatory and conrotatory electrocyclic ring-opening pathways where the BN unit is only a bystander. Two more favourable paths are stepwise and involve 1,3-boron–carbon interactions. The lowest energy barrier for the isomerisation reaction, 22 kcal mol−1, should be high enough for an experimental observation in solution. However, in solution the dimerisation of 3 is computed to have a very low barrier (3 kcal mol−1), and thus 3 is expected to be a short-lived reactive intermediate.
Keywords: ab initio; azaborine; BN aromatics; Dewar isomer; reaction mechanism